The Influence of Religiosity and Ideology on Customer Commitent at lapis talas Bogor - Nuzila, Hasna -; Nuh, Ahmad; Widodo, Andrian A (Universitas Indraprasta PGRI Jakarta, 2024)
This study aims to examine the influence of religiosity and ideology on customer commitment to Lapis Talas Bogor products. In this context, religiosity refers to the extent to which religious values influence purchasing decisions, while ideology pertains to the beliefs or views related to the consumer's cultural and social identity. The research method employed includes surveys and interviews with Lapis Talas Bogor customers, consisting of both local consumers and tourists. The findings show that religiosity has a significant impact on consumer loyalty and purchasing decisions, particularly regarding halal certification, which enhances trust among Muslim consumers. Furthermore, the ideology embedded in local products, such as the reinforcement of Bogor's cultural identity, also contributes to customer commitment. This study concludes that the integration of religiosity and ideology in marketing strategies can enhance customer commitment and loyalty, as well as contribute to the market sustainability of Lapis Talas Bogor.